Spatiotemporal Dynamics of Landscape Transformation in Western Balkans’ Metropolitan Areas - Isra Hyka; Artan Hysa; Sokol Dervishi; Marijana Kapovic Solomun; Alban Kuriqi; Dinesh Kumar Vishwakarma; Paul Sestras (Land, 2022)
Human-caused landscape transformation represents a danger to conserving the Earth’s natural habitats. Landscape fragmentation (LF) caused by transportation infrastructure and urban development poses a threat to human and environmental health by increasing traffic noise and pollution, reducing the size and viability of wildlife populations, facilitating the spread of invasive species, and reducing the recreational qualities of the landscape. It is especially noticeable in the metropolitan areas of developing countries due to rapid and unsupervised urban sprawl. In this context, this study aims to protect natural landscapes and biodiversity, promoting forms of sustainable development. To exemplify our aim, we bring a spatio-temporal analysis of landscape change comparing three metropolitan areas in the Western Balkans (WB). First, we compare the land use land cover (LULC) changes in Tirana (Albania), Skopje (North Macedonia), and Sarajevo (Bosnia and Herzegovina). The comparison was based on the Urban Atlas (UA) data of 2012 and 2018. The analysis was performed on two levels, at the metropolitan and urban spatial scales. Apart from descriptive statistics about the changes in surface area and patch counts, we used effective mesh size (meff) as a landscape metric to quantify the LF level. Our results show that each city has faced significant LULC change between 2012 and 2018, with a dominant increase in artificial surfaces. Furthermore, the cumulative natural surface area reduction is followed by increased landscape patch counts, indicating an increased LF at both levels. This study enhances public awareness about the landscape transformation trends in the developing metropolitan regions of WB. The respective administrative bodies at both local and central levels are invited to consider our results and adopt proper measurements to reduce the adverse consequences of subsequent spatial development decisions.